Pendekatan Teoritis Kriminologi terhadap Pola Perilaku dan Faktor Penyebab Korupsi - Nida Fauziah Hasanah; Oci Senjaya (Universitas Cokroaminoto Yogyakarta, 2026)
This study examines patterns of corrupt behavior in Indonesia using criminological theories such as anomie, social control, differential association, and crime opportunity. Corruption in Indonesia is categorized as an extraordinary crime involving abuse of power for personal gain,with widespread political, economic, and socio-cultural impacts. This study uses a juridical-empirical method with a normative approach to understand the causes of corruption through analysis of legal and criminological literature. There are several main factors that cause high rates of corruption in Indonesia, namely internal factors such as individual personality and personal behavior, and external factors such as the social and cultural environment, and weaknesses in the legal system. This study shows that corruption cannot only be overcome with repressive measures but also requires preventive measures through the control of criminogenic factors.